Aggressive Quarantine Measures Reduce the High Morbidity of COVID-19 in Patients on Maintenance Hemodialysis and Medical Staff of Hemodialysis Facilities in Wuhan, China - Junhua Li; Yi Yang; Meiling Gong; Jia Shi; Xi Zhou; Xue Xing; Hao Pan; Shuiming Guo; Xiaoyan Chang; Anying Cheng; Yanan Wang; Shuwang Ge; et al. (Karger Publishers, 2020)
Introduction: Maintenance hemodialysis (MHD) patients are highly vulnerable to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Medical staff of dialysis facilities without sufficient biosecurity protection are susceptible once exposed to asymptomatic coronavirus disease 2019 (COVID-19) patients. This study evaluated the epidemiological characteristics of COVID-19 in all MHD patients and medical staff of dialysis facilities in Wuhan, China. Methods: We collected COVID-19 morbidity and mortality data from MHD patients and medical staff from 52 hemodialysis centers in Wuhan. Then, we analyzed the symptoms and signs of patients and staff in our hospital (Tongji Hospital in Wuhan), and chest CT, SARS-CoV-2 nucleic acid detection and laboratory tests were performed. After aggressive quarantine of the COVID-19 patients, we followed up on the prognosis of them. Results: We analyzed the hemodialysis data from Wuhan and found that 10% of MHD patients and 6.0% of medical staff were suspected of COVID-19. Further detection of SARS-CoV-2 nucleic acid showed that 1.7% of MHD patients and 2.9% of medical staff were confirmed as having COVID-19. In our facility, 18.9% (46/244) of patients and 9.5% (6/63) of medical staff were suspected of COVID-19. Among them, 2.9% (7/244) of MHD patients and 4.8% (3/63) of medical staff tested positive for SARS-CoV-2 were confirmed as having COVID-19. Interestingly, 87.0% of MHD patients suspected of COVID-19 did not have obvious symptoms, but the CT screening showed features of viral pneumonia. There were no significant differences in symptoms, CT findings, comorbidity and laboratory findings of SARS-CoV-2 nucleic-acid-positive and -negative patients. We followed up these patients and found that 57 patients with COVID-19 died (COVID-19 mortality 8.9%). Two patients from our dialysis center with COVID-19 (mortality 4.3%) died. No new infections occurred in our dialysis center after aggressive quarantine was initiated. Conclusions: The SARS-CoV-2 infection rates in MHD patients and medical staff in dialysis facilities were both high in Wuhan. Frequent chest CT and SARS-CoV-2 nucleic acid detection were needed to screen COVID-19 patients in dialysis facilities. Through the lessons of this experience on the aggressive diagnosis and quarantine measures of COVID-19 patients, we hope medical staff avoid more infections in serious epidemic areas.